Aliran Ilmu Kalam dan Pokok Pikirannya Masing-masing - Muhammad Zakir Hasibuan; Sapri Sapri (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This research discusses various schools of Kalam science, including Ash'ariyah, Maturidiyah, Mu'tazilah, and Wahhabiyah and examines the core ideas that underlie them. Each school presents a unique approach in understanding humans' relationship with God, freedom and moral responsibility through a combination of rational (aqli) and textual (naqli) arguments. This article explores how the development of theological thought not only enriched the Islamic intellectual tradition, but also shaped the community's response to social and political dynamics throughout history. Using qualitative methods based on literature study, this research analyzes the relevance of these schools of thought in responding to the challenges of the modern era. The research findings emphasize the importance of moderation and tolerance as the main foundation for maintaining harmony in the diversity of Islamic thought. This article provides a fresh perspective that can be a strategic reference in developing inclusive theological discussions amidst the challenges of the contemporary world.